Edukasi Keselamatan Berkendara dalam Menekan Pelanggaran Lalu Lintas Bonceng Tiga di Miftahul Jannah Bandar Lampung - Aditia Arief Firmanto; Dwi Arrasy Aprillia RS; Alif Irfan Wiryawan; Namuda Farellian; Klara Ayu Alvariza; Bunga Syifa Arzila; Sahl Abdullah Al Faruq Arraki (Insan Kreasi Media, 2026)
Traffic accidents involving adolescents remain a major public health and road safety concern in Indonesia. Limited knowledge of traffic regulations and safe riding practices contributes to risky behaviors among students, including the widespread practice of carrying more than one passenger on a motorcycle (three-passenger riding). This community service program aimed to enhance students' understanding of traffic safety regulations and increase legal awareness regarding safe riding practices, particularly the prohibition of three-passenger motorcycle riding. The program was conducted at Pondok Pesantren Tahfidz Quran Miftahul Jannah, Bandar Lampung, involving 50 students. The intervention employed expository learning combined with interactive discussions and question-and-answer sessions. Educational materials were developed based on Law Number 22 of 2009 concerning Traffic and Road Transportation and related literature. Evaluation was conducted through direct observation of participants' engagement and responses during the educational activities. The results showed that, prior to the program, participants' understanding of traffic safety was generally limited to helmet use and avoiding reckless driving. Following the educational activities, participants demonstrated improved understanding of traffic regulations, legal sanctions for traffic violations, ticket (tilang) procedures, and the safety risks associated with three-passenger motorcycle riding.